Peningkatan Pemasaran Produk Kreatif dengan Kemandirian Keuangan - Septiani, Ana; Al Amin, Muhammad Ridho; Kurniawan, Angga; Rahayu, Sri Retnaning; Editya, Dimas Bagus; Fuadi, Slamet (SINAR SANG SURYA, 2025)
The purpose of this activity is to increase financial independence for the majority of residents in Sidodadi Village. The methods applied in this activity are demonstration and direct practice. In this mentoring, there are several activities carried out, namely demonstrations and direct practice on how to make decorative lamps from glass bottles by the presenter, and mentoring in marketing the product. Training is conducted face-to-face and accompanied online. The final session of this activity was filled with material related to the type of activity and provided knowledge and understanding in marketing creative products to increase financial independence. The activities carried out have provided results with indicators that participants understand the empowerment of potential in marketing creative products and managing their own financial independence so that they can innovate the products that will be developed